PASCAOPERASI ADENOMA HIPOFISIS HUBUNGAN ANTARA DURASI AWITAN DENGAN LUARAN KLINIS VISUS DAN LAPANG PANDANG - Renindra Ananda Aman,* Reki Setiawan,* Retno Asti Werdhani,* Samsul Ashari,* David Tandian,* Syaiful (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION PITUITARY ADENOMAS CAN CAUSE DECREASE OF VISUAL ACUITY VA NARROWING VISUAL FIELD VF SEVERAL STUDIES HAVE SHOWED THAT THE DURATION OF COMPLAINTS WERE RELATED SIGNIFICANTLY WITH CLINICAL OUTCOMES AS A NATIONAL REFERRAL CENTER HOSPITAL ALL PITUITARY ADENOMA PATIENTS WHO CAME TO OUR INSTITUTION WERE REFERRED FROM OPHTHALMOLOGISTS NEUROLOGISTS AND NEUROSURGEONS FROM OTHER INSTITUTIONS